Front Cover: Symmetry‐Protected Two‐Level System in the H3 Center Enabled by a Spin–Photon Interface: A Competitive Qubit Candidate for the NISQ Technology (Adv. Quantum Technol. 11/2022). Issue 11 (11th November 2022) - Bian, Guodong; Zhang, Jixing; Xu, Lixia; Fan, Pengcheng; Li, Mingxin; Wu, Chenyu; Li, Jichao; Wang, Hailong; Zhang, Qianfan; Cai, Zhongyu; Yuan, Heng
Abstract : Investigation of promising spin‐qubit candidates in solid materials is vital for scalable noisy intermediate scale quantum (NISQ) technologies. As demonstrated by Hailong Wang, Heng Yuan, and colleagues in article number 2200044, a symmetry‐protected two‐level system (qubit) based on the H3 center in diamond with C 2v symmetry is characterized, which is capable of applications in quantum information processing. The figure depicts an N–V–N geometry (H3 center) in the diamond acting as a spin–photon interface, which can interrogate the spin information of the qubit in the form of fluorescence. The green beam is fluorescence, the oscillation at the bottom represents the evolution of spin states, and the surrounding "0" and "1" elements indicate that this work provides a very competitive processor for quantum computing.